Fenomena FoMO (Fear of Missing Out): Analisis Filsafat Ilmu terhadap konsep kebahagiaan di era media sosial - Haq, Adilla Ulya; Solikhah, Anggun; Sherino, Moh. Mufti Hakim (Maliki Interdisciplinary Journal, 2026)
The Fear of Missing Out (FoMO) phenomenon has become a rapidly growing psychological and social crisis in the social media era. FoMO arises when individuals feel anxious, afraid of missing out on information, or feel less valuable than others who portray their lives ideally on social media. This study aims to analyze the role of philosophy of science in understanding the FoMO phenomenon, specifically through the perspectives of ontology, epistemology, and axiology. From an ontological perspective, social media has transformed the essence of happiness into a digital construct dependent on external validation. From an epistemological perspective, information about happiness is obtained not through direct experience or rational reasoning, but through representations on social media that are often considered truth. Meanwhile, from an axiological perspective, the FoMO phenomenon raises moral and value issues because it increases anxiety, social communication, impulsive behavior, and a decreased quality of life. Based on a study of available journal literature, philosophy of science presents itself as an analytical instrument capable of clarifying the concept of happiness, critiquing digital constructs, and directing individuals towards authentic values ​​and more rational actions. Thus, philosophy plays an important role in helping individuals understand FoMO more deeply and restore the meaning of happiness that is in accordance with human values.